Siderophore receptor and porin protein-based vaccine technology: an intervention strategy for pre-harvest control of Escherichia coli O157 in cattle - Thornton, Ashley B. (Kansas State University, 2007)
Escherichia coli O157:H7 is a human food-borne pathogen and cattle feces are a major source of contamination. Immunization against E. coli O157 may be a practical pre-harvest intervention strategy. A siderophore receptor/porin proteins (SRP) based vaccine has been developed to decrease the prevalence of E. coli O157 in cattle. Two studies were conducted to determine the efficacy of the SRP vaccine. In the first study, thirty calves were randomly assigned to one of two groups: control or SRP vaccine. Two weeks after the second vaccination, calves were orally inoculated with nalidixic acid-resistant (Nal[superscriptR]) E. coli O157. Fecal samples were collected for five weeks. Calves were necropsied on day 35 to collect gut contents and tissue swabs to determine Nal[superscriptR] E. coli O157:H7. The number of calves that were culture positive for E. coli O157 were lower (P= 0.07) in vaccinated group compared to the control. In the second study, cattle in two feedlots were randomized to SRP vaccine or control. Cattle were vaccinated on days 0 and 21. Rectal fecal samples were collected on day 0, and pen floor samples were collected on days 21, 35, and 70. Rectal fecal samples, RAMS, and hide swab samples were collected on d 85. Cattle were weighed on days 0, 21, and 85. Vaccination significantly reduced (P = 0.04) fecal E. coli O157 prevalence. There was also a decrease (P < 0.05) in E. coli O157 prevalence on hides and in fecal samples on day 85 in vaccinated cattle compared to the control.
Keywords: Escherichia coli O157:H7; Vaccine; Cattle; Biology, Microbiology (0410); Biology, Veterinary Science (0778)